2017
DOI: 10.1371/journal.pone.0176501
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin down-regulates the phosphorylation level of Creb and induces apoptosis in human breast cancer cell

Abstract: Polydatin (PD), a component isolated from Polygonum cuspidatum, has a number of biological functions. However, the antitumor activity of PD has been poorly investigated. In this study, the effect of PD on cell proliferation was evaluated by thiazolyl blue tetrazolium bromide assay. Cell cycle distribution and apoptosis were investigated by flow cytometry. The phosphorylation levels of panel of phosphor-kinases were detected by human phospho-kinase arrays. The expression of several proteins associated with cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…PD is known to inhibit proliferation and induce apoptosis in breast cancer and colorectal cancer. 26,27 Therefore, we investigated disrupt the extracellular matrix (ECM) and then induce cancer cell migration and invasion. 28,29 In vitro, increased autocrine vascular endothelial growth factor (VEGF) is also considered to be one of the hallmarks of cancer invasion.…”
Section: Pd Combined With 2-dg Displays a Potent Anti-cancer Activimentioning
confidence: 99%
“…PD is known to inhibit proliferation and induce apoptosis in breast cancer and colorectal cancer. 26,27 Therefore, we investigated disrupt the extracellular matrix (ECM) and then induce cancer cell migration and invasion. 28,29 In vitro, increased autocrine vascular endothelial growth factor (VEGF) is also considered to be one of the hallmarks of cancer invasion.…”
Section: Pd Combined With 2-dg Displays a Potent Anti-cancer Activimentioning
confidence: 99%
“…Chen et al have shown that downregulation of cAMP-response element binding protein (CREB) was associated with inhibition of mammary tumor cell growth by a mechanism that appears to be independent of ER as acting on both triple negative cells (MDA-MB-231) and ER+ cells (MCF-7) 21 . Knowing that this pathway is found activated during resistance to tamoxifen 22 , the effects of this drug on CREB pathway were investigated in EO771 cells.…”
Section: Tamoxifen Activates Signaling Pathways In Eo771 Cellsmentioning
confidence: 99%
“…Notably, all of these pathways were associated with cancer-related diseases, in line with the notion that PD showed the potential as anti-tumor agent. 11,12 Based on target predicting and pathway enrichment analysis, a systematic network was constructed using Cytoscape 3.2.1. As shown in Fig.…”
Section: Go and Kegg Pathway Analysis And Network Constructionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Furthermore, recent studies have shown that PD may act as an anti-tumor agent by inhibiting cell proliferation and inducing apoptosis in a variety of tumors. 11,12 However, current knowledge about the medicinal characteristics as well as the action mechanism of PD is still fragmented, and its system-level mechanism warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%